The Impact of E-banking Entrepreneurship Orientation Drivers on Sustainable Performance: A Case Study of Banks Operating in Kingdom Saudi Arabia - Abderrazak Laghouag (Business Management Analysis Journal (BMAJ), 2022)
Saudi Arabia’s vision for 2030 strives to increase the contribution of SMEs in the national economy from 20% to 35% and reduce the unemployment rate from 11.6% to 7%. To achieve this, the Kingdom relies on the vital role of banks to support entrepreneurial projects. This opportunity raised the competition among the different banks operating in Saudi Arabia to attract more customers and gain significant share market through being more pro-active and innovative and ready to risk-taking regarding e-services. This study aims to measure the impact of e-banking entrepreneurship orientation drivers on a bank’s sustainable performance. A questionnaire has been developed to test the different hypotheses, and 607 responses have been collected and analyzed. The results show high awareness regarding the drivers supporting e-banking entrepreneurial orientation, especially the human capital. On the other hand, the results show the significant positive impact of e-banking entrepreneurial orientation on the sustainable performance dimensions, namely, environmental, ethical, and social performance.